2020
DOI: 10.1021/acsomega.9b04420
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Approach on Oxygen Vacancy-Engineered CeO2 Nanosheets Concocts over an Oyster Shell Manifesting Robust Photocatalytic Activity toward Water Oxidation

Abstract: Lethargic kinetics is the foremost bottleneck of the photocatalytic water oxidation reaction. Hence, in this respect, the CeO 2 coral reef made up of nanosheets is studied focusing on the oxygen vacancy that affects the water oxidation reaction. First, CeO 2 was prepared in an oyster shell/crucible with the presence/absence of urea by a simple calcination technique to tune the oxygen vacancy. More oxygen vacancy was detected in CeO 2 prepared from urea and oyster shell, which is evidenced from Raman and PL ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 73 publications
3
36
0
Order By: Relevance
“…In this technique, successful biosynthesis of CeO2-NPs was confirmed with respect to the color change of the cerium salt solution from light yellow to whitish-brown after the addition of the drops of the plant extract [32]. In addition, creation of a strong absorption spectra at a maximum wavelength of 325 nm due to surface plasmon resulting to the charge transfer from O2P to Ce4f orbitals was another sign of the production of CeO2-NPs (Fig 1), which is highly consistent with the reported results [6,31,32]. Also, the optimization of the conditions for the production of the largest amount of CeO2-NPs with dimensions less than 50 nm was performed by measuring the intensity of the absorption spectra and displacement at the maximum wavelength position by a UV-Vis spectrophotometer.…”
Section: Determination Of Volatile Compoundssupporting
confidence: 89%
See 1 more Smart Citation
“…In this technique, successful biosynthesis of CeO2-NPs was confirmed with respect to the color change of the cerium salt solution from light yellow to whitish-brown after the addition of the drops of the plant extract [32]. In addition, creation of a strong absorption spectra at a maximum wavelength of 325 nm due to surface plasmon resulting to the charge transfer from O2P to Ce4f orbitals was another sign of the production of CeO2-NPs (Fig 1), which is highly consistent with the reported results [6,31,32]. Also, the optimization of the conditions for the production of the largest amount of CeO2-NPs with dimensions less than 50 nm was performed by measuring the intensity of the absorption spectra and displacement at the maximum wavelength position by a UV-Vis spectrophotometer.…”
Section: Determination Of Volatile Compoundssupporting
confidence: 89%
“…The biological synthesis of CeO2-NP was performed according to the common methods reported in the literature [6][7][8] yet with some modifications and optimization in the synthesis effectiveness variable, including the cerium salt concentration, extract volume, temperature, and time. Optimizations in the process of synthesizing CeO2-NP was based on achieving the highest absorption spectra intensity within 300-330 nm (due to charge transfer from O2P to Ce4f orbitals) [31], which was measured and recorded by a UV-Vis spectrophotometer. Under optimum condition, 20 mL of aqueous extract of Pelargonium hortorum, as the reducing agent, was added to 80 mL of 0.1 M cerium solution (2.91 g of Ce(NO3)2.6H2O salt were dissolved in 100 mL double distilled water).…”
Section: Biosynthesis Of Ceo2-npmentioning
confidence: 99%
“…inherent LMCT band among O-2p → Mg-2p/Mg-1s and O-2p → Cr-3dt 2g within 200–390 nm, d–d transitions of Cr 3+ in the band region of 400‒712 nm. The d–d transitions of Cr 3+ ion (d 3 electronic arrangement), comprises of 4A 2g → 4T 1g (F) and 4 A 2g → 4T 2g (F) which were associated to the absorption peaks at 410 and 570 nm, respectively 45 , 93 , 94 . The predominant band of CrO 6 absorption peak in the MgCr-LDH/NP arises owing to the atomic level variation among MgO 6 and CrO 6 with defects riched self-assembled and aggregated nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…The emission peaks at 459 nm could be linked to the radiative recombination of surface trapped localized excitonic charge carriers. The large decrease in PL intensity for MgCr-LDH/NP indicated that the recombination of photogenerated exciton pairs is significantly quenched owing to the large density of formation of defect sites and oxygen vacancies after the structural evolution from bulk to nanosheets and then self-assembling of the nanosheets led to the formation of nanoparticles 91 , 94 . This is related to the dynamic of charge transfer within the MgCr-LDH/NP matrix, which could be helpful to stimulate the PEC properties and corresponding water splitting reaction.…”
Section: Resultsmentioning
confidence: 99%
“…As transferred into normal hydrogen electrode (NHE) potentials, the CB positions of the ZnF and WO 3ÀX samples were evaluated by employing the below conversion equation. 50 E vs. NHE = E Ag/AgCl + 0.0591pH + 0.197 Thus, the CB potential of WO 3ÀX and ZnF were computed to be +0.25 and À0.17 eV (vs. NHE), respectively.…”
Section: Njc Papermentioning
confidence: 99%